2023
DOI: 10.1111/inm.13257
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and risk factors of PTSD symptoms among nurses during the COVID‐19 pandemic—A systematic review and meta‐analysis

Santiago Hernández‐Bojorge,
Adriana Campos,
Jeegan Parikh
et al.

Abstract: Since the first reported outbreak in China, the Coronavirus disease 2019 (COVID‐19) has raised serious concerns globally. The COVID‐19 pandemic has caused a severe psychological impact on healthcare workers (HCWs), and especially nurses, who are the most numerous and exposed frontline group. This systematic review and meta‐analysis aims to summarise extant literature on the effects of the COVID‐19 pandemic on the psychological health of nurses, particularly concerning the prevalence and risk factors for post‐t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 111 publications
0
1
0
Order By: Relevance
“…25 Frontline healthcare workers treating COVID-19 patients are at high risk of experiencing serious psychological effects, such as post-traumatic stress disorder symptoms. [26][27][28] The fact that the prevalence of psychological distress among care workers at elder care facilities is consistent with that of frontline healthcare workers treating COVID-19 patients suggests that the psychological distress suffered by care workers at elder care facilities is considerable. Conversely, a study on psychological distress suffered by family caregivers that was based on similar criteria and was conducted at the same time as the present study revealed a prevalence rate of 39.6%, 29 which is lower than that revealed by this study for care workers at elder care facilities.…”
Section: Discussionmentioning
confidence: 79%
“…25 Frontline healthcare workers treating COVID-19 patients are at high risk of experiencing serious psychological effects, such as post-traumatic stress disorder symptoms. [26][27][28] The fact that the prevalence of psychological distress among care workers at elder care facilities is consistent with that of frontline healthcare workers treating COVID-19 patients suggests that the psychological distress suffered by care workers at elder care facilities is considerable. Conversely, a study on psychological distress suffered by family caregivers that was based on similar criteria and was conducted at the same time as the present study revealed a prevalence rate of 39.6%, 29 which is lower than that revealed by this study for care workers at elder care facilities.…”
Section: Discussionmentioning
confidence: 79%